The ONLINE-TICS Study Protocol: A Randomized Observer-Blind Clinical Trial to Demonstrate the Efficacy and Safety of Internet-Delivered Behavioral Treatment for Adults with Chronic Tic Disorders - Jakubovski, Ewgeni; Reichert, Cornelia; Karch, Annika; Buddensiek, Nadine; Breuer, Daniel; Müller-Vahl, Kirsten (Frontiers in Psychiatry, 2016)
Background: In recent years, behavioral therapy with Comprehensive Behavioral Intervention for Tics (CBIT) has been recognized as an effective and safe treatment in patients with Gilles de la Tourette syndrome. In Germany, however, dissemination of CBIT is restricted due to a considerable lack of well-trained therapists. The aim of this study is to overcome this deficiency by creating a new and sophisticated internet-delivered CBIT (iCBIT) program. With this study, we want to demonstrate that iCBIT is superior to internet-delivered psychoeducation and comparable to face-to-face CBIT. Method and Analysis: This is a multicenter, prospective, randomized, controlled, observer-blind clinical trial, which will be conducted at 5 sites in Germany (ONLINE-TICS). Over the course of 2 years 160 adult patients with chronic tic disorders will be assigned to one of three treatment arms: iCBIT (n=72), online psychoeducation (n=72) or face-to-face CBIT (n=16). All treatments will consist of 8 therapy sessions over a period of 10 weeks and will follow the well-established CBIT manual by Woods and colleagues. The primary outcome measure will be the change in Yale Global Tic Severity Scale (YGTSS) at one week post treatment. Secondary outcome measures include YGTSS change at 3 and 6 months, video- and self-ratings of tics as well as scales for psychiatric comorbidities assessed at each visit. The primary analysis will compare iCBIT to online psychoeducation using a mixed linear model with the YGTSS change as dependent variable. Secondary analyses will look at the comparison between iCBIT and face-to-face CBIT in a non-inferiority analysis. Discussion: If iCBIT proves to be effective, it would be a considerable contribution to close the wide gap in treatment providers for tic disorders not only in Germany, but also in several other countries, since this internet-delivered therapy does not require the supervision of a therapist. In addition, iCBIT would be a cost-effective and readily available treatment alternative that guarantees high quality standard of CBIT. Ethics and Dissemination: All institutional review boards approve the protocol. All participants will provide informed consent. There are no conflicts of interest. After study completion the results will be published. Study Registration: ClinicalTrials.gov Identifier: NCT02413216